Photometric evaluation of cranial and facial symmetry in hemicoronal single suture synostosis treated with surgical fronto-orbital remodeling. Issue 8 (August 2016) - Mazzoleni, Fabio; Meazzini, Maria Costanza; Novelli, Giorgio; Basile, Valentina; Giussani, Carlo; Bozzetti, Alberto
Abstract: Objective: Evaluation of frontal vault symmetry and progressive facial symmetrization in a cohort of patients with hemicoronal single suture synostosis treated with a standardized cranioplasty and rigid fixation. Patients and methods: Fifty-four patients with hemicoronal synostosis operated between 1999 and 2014 were reviewed retrospectively. Pre, immediately postoperative and yearly photographs from the top of the skull and frontal views of the face were taken with the same head position and projection. A photogrammetric method was applied to quantify the pre and postoperative contour changes. The anterior skull hemispheres were traced, divided into two equal parts and the areas were compared. Angular measurements obtained by the intersection of the interpupillary line and the glabella perpendicular vertical line were calculated. The average photographic follow-up was 6.8 years. Range 1–14 years. Results: The average advancement on the affected side was 18 mm (range: 16–23 mm). The pre-surgical cranial area on the affected side was increased on average 14.6 + 2.4% (range: 10–18%). The angular measurements documented the frontal symmetry obtained and the progressive improvement of facial symmetry. Conclusion: Cranioplasty with rigid fixation achieved a stable correction of anterior plagiocephaly leading to subsequent symmetrical facial growth. Photogrammetry allowed fora quantitative long-term validation.